Mosses of Marai Parai Trail, Mount Kinabalu - Monica Suleiman; Andi Maryani A Mustapeng; Rimi Repin; Irmah Anwar (Sabah Parks Nature Journal, 2024)
A total of 109 species and three varieties in 62 genera and 26 families of mosses were collected along the Marai Parai Trail, northwestern part of Mount Kinabalu during a three-day survey in October 2023. This represents about 16% and 14% of mosses reported from Sabah and Borneo, respectively. The families with the highest number of species were Sematophyllaceae, followed by Leucobryaceae and Dicranaceae. Among the 112 taxa of mosses, six species are new records for Mount Kinabalu. In addition, several species are rarely collected in Borneo and restricted to Mount Kinabalu, showing the significant importance of the area within the Kinabalu Park.